One-Step Nucleic Acid Amplification System in Comparison to the Intraoperative Frozen Section and Definitive Histological Examination Among Breast Cancer Patients: A Retrospective Survival Study - Bertozzi, Serena; Londero, Ambrogio P.; Bulfoni, Michela; Seriau, Luca; Agakiza, Diane; Pasqualucci, Alberto; Andretta, Michela; Orsaria, Maria; Mariuzzi, Laura; Cedolini, Carla (Frontiers in Oncology, 2022)
Background: The one-step nucleic acid amplification (OSNA) system is a novel molecular technique, which consents to quick intraoperative detection of sentinel lymph node metastases by the amplification of cytokeratin 19 mRNA. Our study aims to evaluate the OSNA method in comparison with frozen section (FS) and definitive histological examination of the sentinel lymph node biopsy among early breast cancer patients considering disease-free survival (DFS) and overall survival (OS). Methods: In this study, we included all women who underwent sentinel lymph node biopsy (SLNB) for breast cancers classified as TNM stage I and II in our center between January 2005 and January 2017, and the follow up was collected up to January 2019. We divided patients among three groups based on SLNB evaluation: definitive histological examination, intra-operative FS, or OSNA. Results: We included 2412 SLNBs: 727 by definitive histological examination, 697 by FS, and 988 by OSNA. Isolated tumor cells were found in 2.32% of cases, micrometastasis in 9.12%, and macrometastases in 13.64%. Surgical procedure duration was significantly shorter in OSNA than in FS (42.1 minutes ±5.1 vs. 70.1 minutes ±10.5, p <0.05). No significant differences have been observed among the three groups regarding OS, DSF, cumulative local, or distant metastases. In particular 5-year DFS was 96.38% in definitive histology (95% C.I. 95.02-97.75%), 96.37% in FS (95% C.I. 94.98-97.78%), and 96.51% in OSNA group (95% C.I. 95.32-97.72%). Conclusions: No difference in OS and DFS was found comparing OSNA, FS, and definitive histology. Furthermore, reduced operative time was found in the OSNA group.